Finger Print and RFID Based Cashless Payment System Analysis of Satisfaction with Madrasah Tsanawiyah Islamic Boarding School Modern Ummul Quro Al-Islami Santri Services for the 2023-2024 Period - Enang Sulaeman; Trisiladi Supritanto; Hendri Tanjung (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to find out how the cashless payment system is implemented and the factors that influence service satisfaction in implementing the cashless payment system for Madrasah Tsanawiyah Islamic Boarding School Modern Ummul Quro Al-Islami students for the 2023-2024 period. This type of research uses quantitative descriptive methods. Based on tests that have been carried out, the independent variables (Ease, Speed, Security and Sharia) in cashless simultaneously or together have a significant influence on Service Satisfaction with an R-Squared value of 0.571, which means that the independent variable used in this study can describe 57.10% while the remaining 42.90% is caused by other variables outside this study.